The effect of anticancer therapy on anti-hepatitis B antibody titres in patients with haematological malignancies and solid tumours. (June 2016) - Yilmaz, Bahiddin; Erdem, Dilek; Teker, Fatih; Goren, Ibrahim; Yildirim, Beytullah; Kut, Engin; Sarikaya, Derya; Atay, Memis H; Yucel, Idris
Objective: To investigate the effect of immunosuppressive anticancer therapy on titre levels of anti-hepatitis B surface antibodies (anti-HBs) in hepatitis B surface antigen (HBsAg) negative and anti-HBs positive patients with haematological malignancies or solid tumours. Methods: This retrospective study reviewed the medical records of patients with haematological malignancies or solid tumours. Pretreatment HBsAg negative and anti-HBs positive patients were included in the analysis. Anti-hepatitis B core antibody status was used to evaluate vaccinated patients and those with resolved HBV infections. Results: The medical records of 237 patients were reviewed retrospectively. The median anti-HBs titre decreased significantly after anticancer therapy compared with the pretreatment median anti-HBs titre in all patients (71 mIU/ml versus 57 mIU/ml). Anti-HBs titre decreased significantly in patients with haematological malignancies (70 mIU/m versus 37 mIU/ml) and in patients administered rituximab-based chemotherapy (67 mIU/ml versus 33 mIU/ml) following chemotherapy, whereas there was no significant change in patients with solid tumours. After chemotherapy, patients with low pretreatment anti-HBs titres (<100 mIU/ml) were more likely to become seronegative (<10 mIU/ml). Conclusion: High levels of anti-HBs may have a protective effect against the reactivation of HBV especially in patients with haematological malignancies who received immunosuppressive anticancer therapy.